SISTEM HUKUM DALAM EKONOMI - Semmawi, Ramli (IAIN Sultan Amai Gorontalo, 2015)
This Paper aims to choose which one economic system of law better to solve our economic problem in Indonesia contests. The research uses monism and dualism system in law to finding the best choice in economic system of law in Indonesia. The research conclusion that Indonesia is better to choose dualism system in economic law to protect his citizen from liberalism in economic global contests.Â State has the duty of protects and gives opportunity in economic access to bring into reality âwelfare all public of Indonesia citizen.